2007
DOI: 10.1093/ajcn/85.6.1650
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and blood pressure change over 5-y follow-up in the SU.VI.MAX cohort

Abstract: These results suggest that high fruit and vegetable intakes may be associated with a lower increase in BP with aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
95
2
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 38 publications
14
95
2
6
Order By: Relevance
“…The other cohort study was conducted in France (SU.VI.MAX; SUpplementation en VItamines et Minéraux AntioXydants study) and included 2341 men and women followed-up for 5?4 years. They reported that the DASH pattern was inversely associated with changes in average BP, but no assessment was reported about the incidence of hypertension (7) . We are aware that our study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other cohort study was conducted in France (SU.VI.MAX; SUpplementation en VItamines et Minéraux AntioXydants study) and included 2341 men and women followed-up for 5?4 years. They reported that the DASH pattern was inversely associated with changes in average BP, but no assessment was reported about the incidence of hypertension (7) . We are aware that our study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…A value of 1 was given to men consuming from 5 to ,30 g alcohol/d and to women consuming from 2?5 to 15 g alcohol/d exclusively from red wine. Participants were categorized into a low (0-2), intermediate (3)(4)(5)(6) or high adherence (7)(8)(9) to this MMDS.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…In total, data 19,21,22,[24][25][26] The types of dairy intake that were examined and definitions of dairy categories differed across studies, as described in Table S2.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In 3 studies, findings were presented as odds ratios, whereas incident HTN occurred in >10% of the study participants. 21,24,26 Because of the high HTN incidence, the odds ratios may present an overestimation of the true RR in these studies, and we, therefore, attenuated the odds ratios using a previously published correction method. 28 In the American studies, dairy intakes were presented in servings per day 20,23 or in times per day.…”
mentioning
confidence: 99%
“…Participants from the SU.VI.MAX (Supplementation en Vitamines et Minéraux Antioxydants) cohort who achieved the current daily fruit and vegetable intake recommendations within the DASH diet guidelines presented a lower increase in blood pressure with aging (Dauchet et al, 2007). In addition, a prospective study in the EPIC (European Prospective Investigation into Cancer and Nutrition) cohort evidenced that a high vegetables, legumes, and fruit diet was associated with a reduced risk of all-cause mortality, especially deaths due to cardiovascular disease underling the recommendation for the diabetic population to eat large amounts of vegetables, legumes, and fruit (Nothlings et al, 2008).…”
Section: Diets With Recognized Benefits On Oxidative Stress and Healtmentioning
confidence: 99%